DIGITAL MARKETING AS AN INTEGRATED MARKETING COMMUNICATION STRATEGY IN BADAN USAHA MILIK DESA (BUMDesa) IN EAST JAVA - Bambang Setiyo Pambudi; Suyono Suyono (Universitas Trunojoyo Madura, 2019)
The purpose of this study is how the marketing communication strategy through digital marketing is carried out by BUMDesa businesses as a driver of the village economy in order to prosper the Village Communities in East Java in marketing their products. This research is focused on the online media such as Instagram Business, Facebook Business and Whatshapp Business.This study used qualitative research methods to provide data and facts about the application of digital marketing in Badan Usaha Milik Desa (BUMDesa). Interviews, documentation, and observation used as data collection techniques. Data is analyzed with a grounded theory approach that provides development of the field of research studies. The analysis techniques consisted of data reduction, data presentation and conclusion.The research findings show that in marketing BUMDesa products, marketing trends are shifting from conventional (offline) to digital (online). The concept of digital marketing for BUMDesa businesses is to be able to market their products from anywhere and anytime through the internet / online media. So the communication strategy is done through digital marketing are the submission of positioning statements in each post on online media (Instagram Bisnis, Facebook Bisnis and Whatshap Bisnis) and the speed of response to online reviews of online media. Suggestions for BUMDesa in carrying out marketing activities, both conventional and especially digital marketing, can be developed for better management.